Old Testament parallels : laws and stories from the ancient Near East - Matthews, Victor Harold; Benjamin, Don C. (New York/Mahwah, N.J.: Paulist Press, 1997)
Old Testament Parallels is a classroom edition of the newest and freshest translations of famous stories. This illustrated text is short and easy to use, and clearly explains the relationship between individual stories and their Bible parallels. Old Testament Parallels is an important resource for study of the Old Testament in all situations.
Outline of Egyptian History from 3100-332 BCE
Includes bibliographical references and index
Keywords: Bible. O.T. -- Extra-canonical parallels; Middle Eastern literature -- Relation to the Old Testament; Law, Ancient -- Sources; Law -- Middle East -- Sources; Bible. O.T. -- History of contemporary events -- Sources; Bible. O.T. -- Antiquities; Middle Eastern literature -- Translations into English; Middle East -- History -- To 622 -- Sources